Ethylbenzene dehydrogenation catalyst as well as preparation method and application thereof
By using modified elolite as a support composite metal oxide catalyst, combined with Sc element synergistic action, the problems of uneven dispersion and low utilization of traditional catalysts were solved, and efficient and stable ethylbenzene dehydrogenation reaction was achieved. , suitable for industrial applications.
Patent Information
- Application Number
- CN202310819174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-07-05
AI Technical Summary
Traditional Fe-K-based oxide catalysts have problems such as uneven dispersion of active sites, low utilization rate, and poor thermal stability in the ethylbenzene dehydrogenation reaction, which cannot meet the needs of industrial applications.
The composite metal oxide catalyst with eloite as the support is used to modify eloite by ball milling molten salt method to form a sheet-like structure, combined with Sc elements to improve catalytic activity and selectivity, and the catalyst is prepared by impregnation method. Achieve uniform dispersion and high stability of the active components.
It significantly improves the catalytic activity, selectivity and stability of the catalyst, reduces production costs, is suitable for large-scale industrial applications, and improves the efficiency and resource utilization of ethylbenzene dehydrogenation reaction.
Smart Images

Figure CN119259066A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dehydrogenation catalysis, and specifically relates to an ethylbenzene dehydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] Styrene is one of the important basic organic raw materials. It is widely used in the fields of synthetic resins and synthetic rubbers. It can also be used in the pharmaceutical, dye, pesticide and mineral processing industries. Its uses are very wide. In commercial applications, it is generally produced by catalytic dehydrogenation of ethylbenzene at a temperature of 600-700°C using a composite oxide catalyst in the presence of a large amount of superheated steam. The catalytic dehydrogenation of ethylbenzene has always been the main technical route for the production of styrene, and its production capacity accounts for about 85% of the total styrene production capacity. The most important core technology in the method of catalytic dehydrogenation of ethylbenzene to produce styrene is the high-performance ethylbenzene dehydrogenation catalyst to produce styrene.
[0003] CN115138356A discloses a catalyst for ethylbenzene dehydrogenation to styrene, which uses nanodiamond treated at high temperature as a nanocarbon carrier and selects precious metal Pd as an active component. The catalyst shows excellent catalytic activity. However, the high cost and easy poisoning of precious metal catalysts limit their further industrial large-scale application. At present, the most widely used and catalytic performance is the Fe-K-based composite oxide catalyst, which has received strong attention from researchers. The ethylbenzene dehydrogenation reaction is carried out under the catalytic action of iron potassium-based oxide catalysts under high temperature and excessive water vapor. The addition of water vapor is mainly to provide and transfer heat, and to eliminate carbon deposits generated during the reaction that will cause the catalyst activity to decrease. The disadvantage of this reaction process is that the energy consumption is too high, and the consumption of a large amount of water resources is also contrary to the development concept of energy conservation and environmental protection. With the continuous increase in the demand for styrene in recent years, people have added elements such as cerium, molybdenum, and manganese to traditional iron potassium oxide catalysts, which have improved the catalytic performance of ethylbenzene dehydrogenation catalysts to a certain extent.
[0004] The basic components of the catalyst for the dehydrogenation of ethylbenzene to produce styrene are a main catalyst, a co-catalyst, a porogen, a reinforcing agent, and the like. CN106582682A discloses a method for synthesizing and preparing a Fe-K-based oxide catalyst. CN108203365B, CN109569640A, and CN108097260A disclose methods for improving the catalytic performance of the catalyst such as activity, selectivity, and stability by adding other promoters. However, there are still some problems with the traditional Fe-K-based oxide catalyst, such as a small specific surface area, uneven dispersion of active sites and low utilization rate, unstable active sites, and the like. The benefits of the methods so far are not obvious, and cannot fully meet the various requirements in the practical application of the catalyst for the dehydrogenation of ethylbenzene to produce styrene. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an ethylbenzene dehydrogenation catalyst and a preparation method and application thereof. The catalyst has the characteristics of uniform dispersion of active components, good thermal stability and simple preparation process, and is suitable for large-scale industrial production. The catalyst is applied to the ethylbenzene dehydrogenation reaction and has high catalytic activity, selectivity and good stability.
[0006] The first aspect of the present invention provides an ethylbenzene dehydrogenation catalyst, which comprises, based on the total mass of the catalyst and calculated by mass fraction, 55% to 68% of carrier halloysite; 32% to 45% of active components; the active components are composite metal oxides.
[0007] According to the present invention, based on the total mass of the composite metal oxide and calculated by mass fraction, the composite metal oxide includes the following components:
[0008] a. 59% to 77% Fe2O3;
[0009] b. 8% to 14.5% K2O;
[0010] c. 4.8% to 12.8% CeO2;
[0011] d. 0.7% to 4.8% MoO3;
[0012] e. 2.6% to 5.9% ZrO2;
[0013] f. 0.6% to 1.8% BaO;
[0014] g. 0.1% to 1.2% Na2O.
[0015] h. 0.8% to 4% Sc2O3.
[0016] According to the present invention, preferably, the halloysite is ball-milled molten salt modified halloysite.
[0017] According to the present invention, in the ethylbenzene dehydrogenation catalyst, the halloysite is modified by ball milling molten salt method, and the tubular halloysite carrier is expanded into a flaky halloysite carrier with a rough surface rich in defects.
[0018] According to the present invention, the halloysite is shown as flakes and tubes in the TEM morphology. In the TEM morphology, based on the total area of the tubular halloysite and the flake halloysite, the proportion of the halloysite nanosheets is more than 58%, preferably 58% to 94%, and more preferably 58% to 92%.
[0019] The second aspect of the present invention provides a method for preparing the above-mentioned ethylbenzene dehydrogenation catalyst. The preparation method is an impregnation method, preferably a wet impregnation method. The method comprises the steps of dispersing halloysite in an active component source, and then drying and calcining to obtain the catalyst.
[0020] According to the present invention, preferably, the halloysite is ball-milled molten salt modified halloysite, that is, the halloysite modified by the ball-milling method and the molten salt method. The ball-milling molten salt method modification step includes the steps of uniformly mixing the sodium salt and the halloysite, ball-milling, roasting, washing, and drying; the sodium salt includes sodium nitrite and sodium bicarbonate.
[0021] According to the present invention, in the ball milling molten salt method, the mass ratio of sodium bicarbonate to sodium nitrite is 0.08 to 0.35, and the mass ratio of sodium salt to halloysite is 5.6 to 7.8.
[0022] According to the present invention, in the ball milling molten salt method, the sodium salt also includes sodium phosphate. Preferably, the mass ratio of sodium phosphate to sodium nitrite is 0.01 to 0.60, preferably 0.08 to 0.50.
[0023] According to the present invention, in the ball milling molten salt method, the ball milling uses grinding balls with a diameter of 3 to 6 mm, preferably zirconium oxide balls, the ball milling speed is 300 to 400 rpm, and the ball milling time is 60 to 90 min.
[0024] According to the present invention, in the ball milling molten salt method, the calcination atmosphere is an air atmosphere; and / or the calcination temperature is 350-550° C.; and / or the calcination time is 2-5 hours. The heating rate during the heating to the calcination temperature is 1-8° C. / min.
[0025] According to the present invention, in the ball milling molten salt method, the washing liquid is preferably deionized water. The filtrate is washed until it is neutral to ensure that the soluble salts in the sample are completely removed and must be washed to neutrality after roasting. Preferably, the neutral pH range is 6.75 to 7.35.
[0026] According to the present invention, in the ball milling molten salt method, the drying temperature is 60 to 100° C.; and / or the drying time is 8 to 15 hours.
[0027] According to the present invention, in the preparation method of ethylbenzene dehydrogenation catalyst, water is added to the active component source and then halloysite is dispersed. Preferably, the solid-liquid ratio of the active component source to the added water is 1 g / 3 to 9 mL.
[0028] According to the present invention, in the preparation method of the ethylbenzene dehydrogenation catalyst, the mixture obtained after dispersing halloysite in the active component source is subjected to water evaporation. The evaporation is preferably carried out in a rotary evaporator; more preferably, the evaporation temperature is 45 to 60° C.; and the evaporation time is 45 to 120 minutes.
[0029] According to the present invention, in the method for preparing an ethylbenzene dehydrogenation catalyst, the drying temperature is 60 to 100° C.; and / or the drying time is 8 to 12 hours.
[0030] According to the present invention, in the preparation method of ethylbenzene dehydrogenation catalyst, the calcination atmosphere is air atmosphere; and / or, the calcination temperature is 500-800°C; and / or, the calcination time is 2-5h; and / or, the heating rate during the process of heating to the calcination temperature is 1-5°C / min. After reaching the calcination temperature, a certain calcination time is maintained.
[0031] According to the present invention, in the method for preparing an ethylbenzene dehydrogenation catalyst, the active component sources include Fe source, K source, Ce source, Mo source, Zr source, Ba source, Na source and Sc source.
[0032] According to the present invention, in the preparation method of ethylbenzene dehydrogenation catalyst, the Fe source includes one or more of ferric oxide, ferric chloride, ferric acetate, ferric nitrate and ferric sulfate; and / or, the K source includes any one or more of potassium carbonate, potassium bicarbonate, potassium nitrate, potassium chloride and potassium sulfate; and / or, the Ce source includes one or more of cerium carbonate, cerium oxalate, cerium nitrate, cerium acetate, cerium chloride and cerium sulfate; and / or, the Mo source includes one or two of ammonium molybdate and phosphomolybdic acid; and / or, the Zr source includes one or more of zirconium carbonate, zirconium acetate, zirconium nitrate, zirconium oxalate or zirconium oxychloride; and / or, the Ba source includes one or more of barium oxide, barium carbonate, barium nitrate, barium sulfate, barium chloride and barium hydroxide; and / or, the Na source includes one or two of sodium carbonate and sodium bicarbonate. The Sc source is an oxide of Sc and / or a Sc salt. The Sc source includes one or more of scandium oxide, scandium chloride, scandium oxalate and scandium acetate.
[0033] According to the present invention, the catalyst prepared by the above method is a powder, which can be subsequently extruded into a monolithic catalyst for industrial ethylbenzene dehydrogenation to styrene reaction. Preferably, the catalyst after molding is a particle with a diameter of 2 to 5 mm and a length of 3 to 10 mm. Water can be added or evaporated as needed during the molding process. After molding, it can be dried at a temperature of 60 to 180° C.; and / or, the drying time is 8 to 20 hours.
[0034] The third aspect of the present invention provides the use of the above ethylbenzene dehydrogenation catalyst or the catalyst prepared by the above preparation method in the reaction of dehydrogenating ethylbenzene to produce styrene.
[0035] According to the present invention, the application uses ethylbenzene as a raw material, and the raw material is contacted with an ethylbenzene dehydrogenation catalyst to react to obtain styrene.
[0036] According to the present invention, the application conditions are: the reaction pressure is 20-100 kPa; the mass space velocity of ethylbenzene is 0.2-2.0 h -1 ; The reaction temperature is 580-640°C; The water ratio (wt) is 1.0-2.0.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] (1) In the catalyst of the present invention, the catalyst comprises: based on the total mass of the catalyst, calculated by mass fraction, 55% to 68% of the carrier halloysite; 32% to 45% of the active component; the active component is a composite metal oxide; the composite metal oxide comprises Fe2O3, K2O, CeO2, MoO3, ZrO2, BaO, Na2O and Sc2O3. The catalyst is a supported catalyst. Compared with the traditional mechanical mixing catalyst, the dispersion of the metal oxide active component is more uniform and good, and nanoparticles with relatively small particle size can be obtained. In the reaction of ethylbenzene dehydrogenation to styrene, the number of accessible active sites of the catalyst is significantly increased, and the utilization rate of the metal oxide component is greatly improved. The catalyst composition of the present invention includes the Sc element. The Sc element has a synergistic effect with the Al site of halloysite, which can promote the surface adsorption of the reactants and improve the catalytic performance of the ethylbenzene dehydrogenation catalyst.
[0039] In the catalyst of the present invention, the use of the halloysite carrier treated by the ball milling molten salt method, in particular, the supported catalyst prepared by ball milling by co-modification with sodium nitrite, sodium bicarbonate and sodium phosphate. The halloysite carrier modified by the ball milling molten salt method is expanded from a tubular structure to a sheet structure, with a rough surface and rich in defect sites. It is applied to the reaction of dehydrogenating ethylbenzene to produce styrene, and has high catalytic activity, selectivity and good stability.
[0040] The catalyst of the present invention uses natural tubular halloysite as a catalyst carrier raw material, which has the characteristics of being cheap, easy to obtain, and abundant in reserves, and the supported catalyst reduces the usage of the metal oxide active component, which can reduce the production and preparation cost of the ethylbenzene dehydrogenation to styrene catalyst. The catalyst has the advantages of high catalytic activity and selectivity, good stability, and the preparation process is relatively simple and stable, and can be applied on a large scale to the ethylbenzene dehydrogenation to styrene reaction.
[0041] (2) In the preparation method of the catalyst of the present invention, halloysite is used as a carrier, and in particular, the halloysite is modified by a ball milling molten salt method, preferably sodium nitrite, sodium bicarbonate and sodium phosphate are co-modified, and the supported catalyst is prepared by ball milling. The halloysite carrier modified by the ball milling molten salt method is expanded from a tubular structure to a sheet structure, with a rough surface and rich in defect sites. At the same time, the Sc element has a synergistic effect with the Al site of the halloysite, which can promote the surface adsorption of the reactant and improve the catalytic performance of the ethylbenzene dehydrogenation catalyst.
[0042] (3) In the application of the present invention, the catalyst is suitable for the dehydrogenation of ethylbenzene to produce styrene, and has the advantages of high catalytic activity, high selectivity and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a TEM test photograph of the ethylbenzene dehydrogenation catalyst obtained in Example 1 of the present invention.
[0044] Figure 2 This is a TEM test photograph of the ethylbenzene dehydrogenation catalyst obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0045] In order to more clearly explain the present invention, the following embodiments are given, but the present invention can be implemented in a manner not limited to the scope of the embodiments.
[0046] The catalyst prepared by the above method was evaluated for activity in an isothermal fixed bed. For the activity evaluation of the catalyst for dehydrogenation of ethylbenzene to produce styrene, the process is briefly described as follows:
[0047] Deionized water and ethylbenzene are respectively fed into the preheating mixer through metering pumps, and then preheated and mixed into gaseous state before entering the reactor. The reactor is heated by electric heating wire to reach the set temperature. The reactor is a stainless steel tube with 100 mL of catalyst filled inside. The reactants flowing out of the reactor are condensed with water and analyzed for their composition by gas chromatography.
[0048] The ethylbenzene conversion rate and styrene selectivity are calculated according to the following formula:
[0049]
[0050]
[0051] In the present invention, the TEM test instrument in each example is JEM-200CX of JEOL Company of Japan. Based on the total area of tubular halloysite and flaky halloysite, the proportion of halloysite nanosheets to total halloysite is obtained by statistics and calculation from the TEM morphology photos and geometric structure characteristics of the catalyst sample, that is, the proportion of observed halloysite nanosheets to total halloysite. Total halloysite is the sum of halloysite nanotubes and halloysite nanosheets.
[0052] In the present invention, the composition of each ethylbenzene dehydrogenation catalyst and the evaluation results of the reaction for 100 hours are shown in Table 1. The stability evaluation results of the ethylbenzene dehydrogenation catalysts of Examples 1, 3, 10 and Comparative Examples 1 and 3 are shown in Table 2.
[0053] Example 1
[0054] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1.1g of halloysite. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0055] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0056] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The TEM test image of the catalyst is shown in Figure 1 The proportion of halloysite nanosheets to total halloysite was 90%.
[0057] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0058] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction for 100h are shown in Table 1. The results of catalyst stability evaluation are shown in Table 2.
[0059] Example 2
[0060] Weigh 5g of sodium nitrite, 2.85g of sodium phosphate and 1.6g of sodium bicarbonate and grind them in a mortar, then add 1.4g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0061] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0062] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to the total halloysite is 62%.
[0063] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0064] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0065] Example 3
[0066] Weigh 5g of sodium nitrite, 0.25g of sodium phosphate and 0.5g of sodium bicarbonate and grind them in a mortar, then add 0.85g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0067] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0068] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C in an air atmosphere for 3 hours at a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 65%.
[0069] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0070] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction for 100h are shown in Table 1. The results of catalyst stability evaluation are shown in Table 2.
[0071] Example 4
[0072] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1.5g of sodium bicarbonate and grind them in a mortar. Then add 1.2g of halloysite. Mix the four substances evenly and ball mill for 75min. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0073] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0074] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 73%.
[0075] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0076] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0077] Example 5
[0078] Weigh 5g of sodium nitrite, 2.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar, then add 1.25g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0079] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0080] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 78%.
[0081] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0082] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0083] Example 6
[0084] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 0.5g of sodium bicarbonate and grind them in a mortar, then add 1.05g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0085] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0086] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 83%.
[0087] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0088] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0089] Example 7
[0090] Weigh 5g of sodium nitrite, 0.4g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar, then add 0.95g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0091] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0092] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to the total halloysite is 80%.
[0093] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0094] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0095] Example 8
[0096] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1g of halloysite. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature of 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0097] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0098] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 88%.
[0099] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0100] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0101] Example 9
[0102] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar, then add 1.3g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0103] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0104] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C in an air atmosphere for 3 hours with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 81%.
[0105] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0106] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0107] Example 10
[0108] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1.1g of halloysite. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0109] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 9.1 parts of cerium oxalate equivalent to CeO2, 3.4 parts of ammonium molybdate equivalent to MoO3, 4.9 parts of zirconium nitrate equivalent to ZrO2, 1.5 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 1 part of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0110] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 89%.
[0111] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0112] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction for 100h are shown in Table 1. The results of catalyst stability evaluation are shown in Table 2.
[0113] Embodiment 11
[0114] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1.1g of halloysite. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0115] Weigh 60.8 parts of ferric oxide equivalent to Fe2O3, 13.7 parts of potassium carbonate equivalent to K2O, 11.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 5.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 3.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0116] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to the total halloysite is 90%.
[0117] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0118] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0119] Example 12
[0120] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1.1g of halloysite. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0121] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0122] Take 200 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 89%.
[0123] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0124] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0125] Comparative Example 1
[0126] Weigh 5g of sodium nitrite, 3.2g of sodium phosphate and 0.35g of sodium bicarbonate and grind them in a mortar, then add 1.55g of halloysite, mix the four substances evenly and ball mill for 75min, the ball diameter is 5mm, and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h, with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0127] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0128] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The TEM test image of the catalyst is shown in Figure 2 The proportion of halloysite nanosheets to total halloysite was 52%.
[0129] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0130] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction for 100h are shown in Table 1. The results of catalyst stability evaluation are shown in Table 2.
[0131] Comparative Example 2
[0132] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1.1g of halloysite. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an 80℃ oven and dried for 12h to obtain modified halloysite.
[0133] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 12.7 parts of potassium carbonate equivalent to K2O, 9.3 parts of cerium oxalate equivalent to CeO2, 3.4 parts of ammonium molybdate equivalent to MoO3, 4.9 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, and 0.6 parts of sodium carbonate equivalent to Na2O and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0134] Take 160 parts of the modified halloysite and disperse them in the mixed solution. After stirring for 30 minutes, the water in the solution is evaporated in a rotary evaporator at 50°C for 80 minutes. The sample is then placed in an oven at 80°C for 10 hours. The dried sample is ground and then calcined at 650°C for 3 hours in an air atmosphere with a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified halloysite as a carrier is obtained. The proportion of halloysite nanosheets to total halloysite is 89%.
[0135] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0136] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction time of 100h are shown in Table 1.
[0137] Comparative Example 3
[0138] Weigh 5g of sodium nitrite, 1.5g of sodium phosphate and 1g of sodium bicarbonate and grind them in a mortar. Then add 1.1g of silica. Mix the four substances evenly and ball mill for 75 minutes. The ball diameter is 5mm and the ball mill speed is 350 rpm. Then the mixed powder is placed in an air atmosphere and calcined at 400℃ for 2.5h with a heating rate of 5℃ / min. After cooling to room temperature of 20℃, the solid sample is repeatedly washed with deionized water until the filtrate is neutral. The washed sample is placed in an oven at 80℃ and dried for 12h to obtain modified silica.
[0139] Weigh 67.8 parts of ferric oxide equivalent to Fe2O3, 11.7 parts of potassium carbonate equivalent to K2O, 8.6 parts of cerium oxalate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 4.4 parts of zirconium nitrate equivalent to ZrO2, 1.3 parts of barium hydroxide equivalent to BaO, 0.6 parts of sodium carbonate equivalent to Na2O, and 2.7 parts of scandium acetate equivalent to Sc2O3 and disperse them in an appropriate amount of water to prepare a mixed solution. The solid-liquid ratio of the solid (active component source) to the amount of water added is 1g / 6mL.
[0140] 160 parts of the modified silica were dispersed in the mixed solution. After stirring for 30 minutes, the water in the solution was evaporated in a rotary evaporator at 50°C for 80 minutes. The sample was then placed in an oven at 80°C for 10 hours. The dried sample was ground and then calcined at 650°C for 3 hours in an air atmosphere at a heating rate of 2°C / min. A composite metal oxide catalyst with ball-milled melt-modified silica as a carrier was obtained.
[0141] After adjusting the water content of the above powder catalyst, it was extruded and pelletized to obtain particles with a diameter of 3 mm and a length of 5 mm. The particles were placed in an oven and dried at 80°C for 4 hours and in an oven at 150°C for 8 hours to obtain a monolithic regular finished catalyst.
[0142] 100 mL of catalyst was loaded into the reactor and the reaction mixture was heated to 40 % under 70 kPa (absolute pressure) and a mass space velocity of 1.0 h-1 of ethylbenzene. -1 The performance evaluation was carried out under the conditions of reaction temperature of 620°C and water ratio of 1.3 (wt). The test results of reaction for 100h are shown in Table 1. The results of catalyst stability evaluation are shown in Table 2.
[0143] Table 1 Ethylbenzene dehydrogenation catalyst compositions of the examples and comparative examples and evaluation results of the reaction time of 100 h
[0144]
[0145] Table 2 Evaluation results of stability of ethylbenzene dehydrogenation catalysts of Examples and Comparative Examples
[0146]
[0147]
[0148] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An ethylbenzene dehydrogenation catalyst, based on the total mass of the catalyst and calculated by mass fraction, the catalyst comprises: 55% to 68% carrier halloysite; 32% to 45% active ingredient; The active component is a composite metal oxide; Based on the total mass of the composite metal oxide and calculated by mass fraction, the composite metal oxide includes the following components: a. 59% to 77% Fe2O3; b. 8% to 14.5% K2O; c. 4.8% to 12.8% CeO2; d. 0.7% to 4.8% MoO3; e. 2.6% to 5.9% ZrO2; f. 0.6% to 1.8% BaO; g. 0.1% to 1.2% Na2O; h. 0.8% to 4% Sc2O3.
2. The catalyst according to claim 1, characterized in that Based on the total area of tubular halloysite and plate-like halloysite, the proportion of halloysite nanosheets is 58% or more, preferably 58% to 94%.
3. The catalyst according to claim 1 or 2, characterized in that The halloysite is modified by ball milling molten salt method.
4. A method for preparing the catalyst according to any one of claims 1 to 3, comprising the steps of dispersing halloysite in an active component source, and then drying and calcining to obtain the catalyst; in, The active component sources include Fe source, K source, Ce source, Mo source, Zr source, Ba source, Na source and Sc source.
5. The preparation method according to claim 4, characterized in that: The halloysite is modified by ball milling molten salt method; the ball milling molten salt method modification step includes the steps of uniformly mixing sodium salt and halloysite, ball milling, roasting, washing and drying; The sodium salt includes sodium nitrite and sodium bicarbonate. Preferably, the sodium salt also includes sodium phosphate.
6. The preparation method according to claim 5, characterized in that: The mass ratio of sodium phosphate to sodium nitrite is 0.01 to 0.60, preferably 0.08 to 0.50; and / or, the mass ratio of sodium bicarbonate to sodium nitrite is 0.08 to 0.35; And / or, the mass ratio of sodium salt to halloysite is 5.6 to 7.
8.
7. The preparation method according to claim 5, characterized in that: The ball mill uses grinding balls with a diameter of 3 to 6 mm; and / or the ball mill speed is 300 to 400 revolutions per minute; and / or the ball mill time is 60 to 90 minutes.
8. The preparation method according to claim 5, characterized in that: In the ball milling molten salt method modification step, the calcination atmosphere is an air atmosphere; and / or the calcination temperature is 350 to 550° C.; and / or the calcination time is 2 to 5 hours.
9. The preparation method according to claim 4, characterized in that: The Fe source includes one or more of ferric oxide, ferric chloride, ferric acetate, ferric nitrate and ferric sulfate; And / or, the K source includes any one or more of potassium carbonate, potassium bicarbonate, potassium nitrate, potassium chloride and potassium sulfate; And / or, the Ce source includes one or more of cerium carbonate, cerium oxalate, cerium nitrate, cerium acetate, cerium chloride and cerium sulfate; And / or, the Mo source includes one or both of ammonium molybdate and phosphomolybdic acid; And / or, the Zr source includes one or more of zirconium carbonate, zirconium acetate, zirconium nitrate, zirconium oxalate or zirconium oxychloride; and / or, the Ba source includes one or more of barium oxide, barium carbonate, barium nitrate, barium sulfate, barium chloride and barium hydroxide; And / or, the Na source includes one or both of sodium carbonate and sodium bicarbonate; And / or, the Sc source includes one or more of scandium oxide, scandium chloride, scandium oxalate, and scandium acetate.
10. The preparation method according to claim 4, characterized in that: The calcination atmosphere is air atmosphere; And / or, the calcination temperature is 500-800°C; And / or, the calcination time is 2 to 5 hours; And / or, the heating rate during the process of heating to the calcination temperature is 1-5° C. / min.
11. Use of the catalyst described in any one of Claims 1 to 3 or the catalyst prepared by the preparation method described in any one of Claims 4 to 10 in the reaction of dehydrogenating ethylbenzene to produce styrene.
Citation Information
Patent Citations
Alkyl-alkenyl arene production catalyst by high-selectivity dehydrogenation of alkyl aromatics
CN101455968A
Nickel-based catalyst, preparation method and application thereof
CN113522295A
Supported catalyst taking halloysite as carrier as well as preparation method and application of supported catalyst
CN113797921A
Dehydrogenation catalyst, preparation method and application thereof, and method for preparing alkenyl arene by dehydrogenating alkyl arene
CN115888745A
Halloysite-based nanocomposites and methods of making and using the same
US20210016250A1